Dampak Mengidolakan K-Pop dan Mengikuti Gayanya dalam Perspektif Fikih Kontemporer - Robiah Robiah; Maya Safarina; Wirdati Saidah (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2026)
The phenomenon of K-Pop as part of global popular culture has significantly influenced the behavior patterns, lifestyles, and identity construction of young Muslims, particularly through practices of idolization and imitation of idols’ lifestyles. Previous studies have not comprehensively addressed this phenomenon from a fiqh perspective, as most existing research focuses on sociological, psychological, and cultural dimensions without a systematic analysis grounded in Islamic law. Therefore, this study aims to examine the impacts of idolizing K-Pop and adopting its styles from the perspective of contemporary fiqh. This research employs a qualitative descriptive approach using a library research method by analyzing primary sources such as fiqh texts, hadith, and scholarly fatwas, as well as secondary sources including academic journals published within the last five years. The findings indicate that practices of idolization and imitation of K-Pop have diverse fiqh implications, depending on intention, context, and their effects on the maqāṣid al-sharī’ah, particularly in terms of preserving religion, morality, and Islamic identity.